Associations of neural error‐processing with symptoms and traits in a dimensional sample recruited across the obsessive–compulsive spectrum. (28th August 2022) - Riesel, Anja; Härpfer, Kai; Thoma, Lars; Kathmann, Norbert; Klawohn, Julia
Abstract: The error‐related negativity (ERN), a neural response to errors, has been associated with several forms of psychopathology and assumed to represent a neural risk marker for obsessive–compulsive disorder (OCD) and anxiety disorders. Yet, it is still unknown which specific symptoms or traits best explain ERN variation. This study investigated performance‐monitoring in participants ( N  = 100) recruited across a spectrum of obsessive–compulsive characteristics ( n  = 26 patients with OCD; n  = 74 healthy participants including n  = 24 with low, n  = 24 with medium, and n  = 26 with high OC‐characteristics). Several compulsivity‐ and anxiety‐associated characteristics were assessed and submitted to exploratory principal axis factor analysis. Associations of raw measures and derived factors with ERN and correct‐related negativity (CRN) were examined. Patients with OCD showed increased ERN amplitudes compared to healthy participants. The ERN was associated with a variety of traits related to anxiety and negative affect. Factor analysis results revealed a most prominent association of the ERN with a composite measure of anxiety and neuroticism, whereas the CRN was specifically associated with compulsivity. Results support differential associations for the ERN and CRN and demonstrate that a dimensional recruitment approach and use of composite measures can improve our understanding of characteristics underlying variation in neural performance monitoring. Abstract : This study adopted a dimensional approach to study transdiagnostic associations of several compulsivity‐ and anxiety‐associated trait characteristics with the error‐related negativity (ERN), a neural response to errors previously linked to several forms of psychopathology. Participants ( N  = 100) were recruited across a spectrum of obsessive‐compulsive characteristics, including a clinical subgroup. Results from correlational and factor‐analyses support differential associations for the ERN and correct‐related negativity (CRN), indicating specific alterations in performance monitoring to be associated with several compulsivity‐ and anxiety‐related characteristics.